Study proposal of the impact of gas flaring on health of communities in Delta state Nigeria - Obi, Nkemdilim; Bwititi, Phillip; Nwose, Ezekiel (International Journal of Scientific Reports, 2021)
Gas flaring is the continuous discharge of gaseous fuel into the atmosphere during oil and gas operations. Over the past years, there has been an increased concern of the impact of gas flaring on the environment and recently on human health. The impact of gas flaring in Niger Delta, Nigeria is of local and global environmental concern. The uncontrolled and wasteful flaring of gas has caused negative impacts on the flora, fauna and human health and livelihood in the region. Reports indicate that gas flaring in Nigeria contributed more greenhouse gases (GHGs) such as carbon dioxide, methane, nitrous oxide, chlorofluorocarbons to the atmosphere than the combined contribution of gas flaring on GHGs in the Sub-Saharan African countries. The GHGs emitted during gas flaring contribute significantly to global warming which may result in sea level rise and hasten the effects of climate change. Gas flaring, commonly carried out by oil exploration companies in Nigeria poses a hazard to the health of populations and environment by pollution, warming and release of GHGs. This study seeked to identify the risks associated with gas flaring in relation to human health in Delta region of Nigeria.